Comparison of Antioxidant and Antibacterial Activities of Camellia Oil From Hainan With Camellia Oil From Guangxi, Olive Oil, and Peanut Oil - Wang, Lanying; Ahmad, Shakil; Wang, Xi; Li, Hua; Luo, Yanping (Frontiers in Nutrition, 2021)
Background/Aim: Camellia oil from Hainan (SY) is a unique vegetable oil in Hainan, China, due to the geographical environment and oil extraction only through simple physical treatments. To compare SY with camellia oil from Guangxi (SC), olive oil (GL) and peanut oil (HS), this study analyzed the antioxidant and antibacterial activity of four vegetable oils. Methods: Using Gallic acid, BHT as the control, Saccharomyces cerevisiae as the model organism, the antioxidant activities of vegetable oils were measured in vitro and in vivo, and the antibacterial activity was measured with the minimum inhibitory concentration (MIC) method. Results: The major contents of SY, SC and HS were oleic Acid; the major content of GL was squalene. The highest total flavonoids content of SY was 39.50±0.41 mg RE/g DW; and the highest total phenolic content of SC was 47.05±0.72 mg GAE/g DW. SY exhibited the strongest scavenging activity of hydroxyl radical (HO·) and superoxide anions (O2-·), the IC50 value were 2.06 mg/mL, 0.62 mg/mL, respectively; and SC showed the strongest DPPH· and ABTS· scavenging activity and the reducing abilities. SY showed excellent effect on survival rate, protection rate, flavonoids uptake of S. cerevisiae cells, decreased MDA content and ROS level, inhibited CAT, POD and GR enzyme activity. The absorption of SC total phenols was the highest by cells. The activity showed GL had a broad-spectrum antibacterial activity. Conclusion: Thus, SY shows potential antioxidant activity and provides an important reference value for people to choose edible vegetable oils.